PENGEMBANGAN KOMPETENSI PENDIDIK PAUD MELALUI DIKLAT KOMPETENSI SOSIAL - Lestariningrum, Anik; Prastihastari W, Intan; Iswantiningtyas, Veny; Yulianto, Dema; Lailiyah, Nur; Kuntjojo, Kuntjojo (UNIVERSITAS PGRI MADIUN, 2019)
Abstract. The objectives to be achieved through this activity are developing the competence of PAUD educators especially their social competencies. This is done in relation to the amount of input from PAUD educators who have difficulties in dealing with the work environment, communicating with colleagues as well as student guardians regarding the presence of PAUD educators who are considered young and have just graduated. The method that will be used in this activity is in the form of training, where participants will be provided with knowledge and learn to practice indicators that hold on to social competence. The training was held for 2 days, this was intended to enable participants to absorb knowledge and implement indicators of social competence through direct practice and independent assignments. Training results were analyzed by questionnaire showing very effective results of 3003, effective 2310, ineffective 1617, and very ineffective 924. Based on the results of the questionnaire calculation the total value was 3212 so it can be said that the implementation of training was very effective. In addition, there were many participants who wrote their suggestions and hopes so that the educator's competency training activities continued continuously. Abstrak. Tujuan yang akan dicapai melalui kegiatan ini yaitu mengembangkan kompetensi pendidik PAUD khususnya kompetensi sosialnya. Hal ini dilakukan terkait banyaknya masukan dari pendidik PAUD yang mengalami kesulitanm dalam hal berhubungan dengan lingkungan kerja, berkomunikasi dengan sejawat juga dengan wali murid terkait adanya pendidik PAUD yang dianggap masih muda dan baru lulus sarjana. Metode yang akan digunakan dalam kegiatan ini berupa diklat dimana peserta akan dibekali pengetahuan dan belajar mempraktekan indikator yang ada berpegangan dengan kompetensi sosial. Diklat ini dilaksanakan selama 2 hari, hal ini dimaksudkan agar peserta mampu menyerap pengetahuan dan mengimplementasikan indikator kompetensi sosial melalui praktek langsung serta tugas mandiri. Hasil diklat dianalisis dengan angket menunjukkan hasil sangat efektif 3003, efektif 2310, tidak efektif 1617, dan sangat tidak efektif 924. Berdasarkan hasil penghitungan angket nilai total sebesar 3212 sehingga dapat dikatakan bahwa pelaksanaan diklat sangat efektif. Selain itu banyaknya peserta yang menuliskan saran serta harapannya supaya kegiatan diklat kompetensi pendidik terus dilakukan secara kontinyu.